2013
DOI: 10.1186/1471-2334-13-461
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous emphysema as the first relevant clinical sign of complicated tubercular lymph node disease in a child

Abstract: BackgroundChildren make up a significant proportion of the global tuberculosis (TB) caseload, and experience considerable TB-related morbidity and mortality. Unfortunately, it is not easy to diagnose TB in the first years of life because of the diversity of its clinical presentation and the non-specific nature of most of its symptoms.Case presentationA 26-month-old male child was admitted to hospital because of the sudden onset of rapidly increasing swelling of the neck, face and upper trunk a few hours before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Some differential diagnoses such as trauma, asthma, and tuberculosis, which are common in our environment and can mimic the presentation of the index patient, were ruled out in the course of managing this patient. A study in Italy has reported that the occurrence of SE may be the first sign of tubercular disease in children [ 8 ]. Another study, although in an adult patient, has documented the occurrence of pneumomediastinum and SE following SARS-CoV-2 infection [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some differential diagnoses such as trauma, asthma, and tuberculosis, which are common in our environment and can mimic the presentation of the index patient, were ruled out in the course of managing this patient. A study in Italy has reported that the occurrence of SE may be the first sign of tubercular disease in children [ 8 ]. Another study, although in an adult patient, has documented the occurrence of pneumomediastinum and SE following SARS-CoV-2 infection [ 9 ].…”
Section: Discussionmentioning
confidence: 99%